Unraveling the genetic diversity and adaptive traits of laboratory pig breeds within the perspective of whole - genome resequencing - Haonan Yuan; Changwen Li; Shengguo Zhao; Yanan Yang; Zhe Chao; Changyou Xia; Jinqiang Quan; Caixia Gao (BMC Genomics)
Abstract As one of the most widely used animal models for human disease research, pigs play a critical role in elucidating disease pathogenesis. However, the genetic characteristics of experimental pig breeds remain underexplored. This study employed whole-genome resequencing to investigate three representative Chinese indigenous pig breeds and two commercial European breeds. Our analysis revealed that indigenous breeds harbor 16.3 million genetic variants (88.3% SNPs), with higher nucleotide diversity compared to commercial breeds. Selective sweep analysis using Fst and π identified key genes under strong selection, including immune regulators (BTK, IL2RG, RASGRP1), metabolic gene MED12, and neuro-associated SDR16C5, with five genes exhibiting significant allele frequency divergence between populations (P < 0.05). Notably, two signature selective regions on chromosome 6 (181,025–182,387 bp and 144,185,871–144,313,689 bp) were identified, containing fixed missense mutations in coat color gene MC1R (p.T305C/p.G283A) and vision-related gene RPE65 (p.G1503A), indicating strong artificial selection for phenotypic traits. This work systematically characterizes the high genetic diversity of Chinese indigenous pigs and their genomic advantages as disease models, providing critical insights for developing precision biomedical animal models.